MENINGKATKAN HASIL BELAJAR DRIBBLE MELALUI MODEL PROBLEM BASED LEARNING DI SMA NEGERI 1 SUNGAI RAYA - Setiawan, Ruli; Haetami, Mimi; Triansyah, Andika (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThe problem discussed in this study is is there any influence of the application of the problem based learning model to the learning outcomes of futsal dribble on students in Sungai Raya 1 High School. The purpose of this study was to determine the effect of the application of the problem based learning model of learning outcomes for futsal dribble learning in students at SMA Negeri 1 Sungai Raya. The study was conducted by classroom action research (PTK). The subjects in this study were students of class XI MIA V SMA Negeri 1 Sungai Raya, with a total of 31 students ,. This research technique uses tests and measurements, which is a test with a measurement instrument lattice measurement of futsal dribble learning outcomes for students in SMA Negeri 1 Sungai Raya. Data analysis uses descriptive percentages. The results of this study indicate there is an increase in futsal dribble learning outcomes in students at SMA Negeri 1 Sungai Raya on XI MIA V students at SMA Negeri 1 Sungai Raya. This is evidenced by an increase in the skills of futsal dribble learning outcomes which is quite good, namely in the first cycle with an average value of 70.43 so an increase of 8.56% from the time of pre-cycle. while the average value in the second cycle is 83.33, so the increase is 22.14%. The conclusion of this study is that there is an increase in futsal dribble learning outcomes through the application of problem based learning models in class X MIA V students of SMA Negeri 1 Sungai Raya . Keywords: Problem Based Learning Model, Dribble Futsal Learning Outcomes.